Strategi Kreatif Produser Buser Investigasi Liputan6 SCTV - Ginting, Andre; Harahap, Machyudin Agung (Jayapangus Press, 2025)
Buser Investigasi Liputan6 SCTV faces a major challenge in maintaining the existence and relevance of its programs amidst the shift in audience preferences towards digital platforms such as YouTube, Instagram, and TikTok. Nielsen March 2023, provided a research that from December 2022 to February 2023, Television always got a number of viewers with a portion that was not larger than cable TV and streaming media, which was around 24.2%. This condition requires television producers to implement innovative creative strategies, not only in presenting news but also in choosing themes, production techniques, and utilizing social media to reach a wider and more diverse audience. The purpose of this study is to examine and analyze what creative strategies are carried out by Buser Investigasi producers and what challenges the producers will face. This study uses a qualitative approach of a qualitative descriptive type in the research period carried out by researchers for 3 months starting from March 2025 to May 2025, by interviewing two producers and one head of a special program. The data collection technique in this study is observation by observing the results of the broadcast, in-depth interviews, and documentation. In data analysis, researchers used data analysis according to Miles & Huberman with three main flows, namely data reduction, data presentation & drawing conclusions. The strategies that have been created and implemented by Buser Investigasi producers include determining the theme, approaching sources, scripts, intonation, editing, and utilizing digital platforms. In this study, it was found that Buser Investigasi producers can apply creative strategies well and on target.